Autoimmunity in Amyotrophic Lateral Sclerosis: Past and Present - Pagani, Mario Rafael (2011)
Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease affecting particularly motor neurons for which no cure or effective treatment is available. Although the cause of ALS remains unknown, accumulative evidence suggests an autoimmune mechanism of pathogenesis. In this paper, we will summarize the current research related to autoimmunity in the sporadic form of ALS and discuss the potential underlying pathogenic mechanisms and perspectives. Presented data supports the view that humoral immune responses against motor nerve terminals can initiate a series of physiological changes leading to alteration of calcium homeostasis. In turn, loss of calcium homeostasis may induce neuronal death through apoptotic signaling pathways. Additional approaches identifying specific molecular features of this hypothesis are required, which will hopefully allow us to develop techniques of early diagnosis and effective therapies.